O PROBLEMIE POROZBIOROWYCH DZIEJÓW III STATUTU LITEWSKIEGO W POLSKIEJ LITERATURZE HISTORYCZNOPRAWNEJ - Sławomir Godek (Zeszyty Prawnicze)
Post-Partition History of the Third Statute of Lithuania Problem in the Polish Historical-Legal Literature